The origin of platinum group minerals in oceanic crust - Evans, Katy; Reddy, Steven; Merle, R.; Fougerouse, Denis; Rickard, William; Saxey, David; Park, J.W.; Doucet, Luc; Jourdan, Fred (2023)
Highly siderophile elements (HSEs), including Re and Os, are used extensively as geochemical tracers and geochronometers to investigate the formation and evolution of Earth's crust and mantle. Mantle rocks are commonly serpentinized, but the effect of serpentinization on the distribution of HSEs is controversial because HSEs are commonly hosted by rare, micrometerto sub-micrometer-scale grains of platinum group minerals (PGMs) of ambiguous origin that are challenging to identify, characterize, and interpret. In this study, atom probe tomography (APT) is used to characterize two spatially close PGM grains hosted by a partially serpentinized harzburgite from Macquarie Island, Australia. The APT data reveal an extraordinary level of detail that provides insights into the origin of a complex Cu-Pt alloy grain (average composition ~Cu4Pt). The grain hosts Fe-, Ni-, and Pt-rich sub-grains associated with Rh, variably overlapping networks of Pd- and Cd-enrichment, and OH-rich volumes identified as fluid inclusions. Osmium and Ru are hosted by an idioblastic laurite (RuS2) grain. Compositional, textural, and phase-diagram constraints are consistent with a modified pre-serpentinization origin for the PGMs, and a comparison between observed and calculated grain distributions indicate that while Os isotope ratios were probably unaffected by serpentinization, whole-rock and grain-scale HSE and isotopic ratios may have been decoupled during serpentinization.